Determination of spray dates for the control of the first generation of Quadraspidiotus perniciosus in Northern Greece - Kyparissoudas, D.S. (ENTOMOLOGIA HELLENICA, 1990)
During 1986-1988 the relationship between catches of San Jose scale (SJS), Quadraspidiotus perniciosus (Comstock), adult males in pheromone traps and crawlers on sticky-tape traps was studied as a basis of SJS crawler control in apple orchards of Northern Greece. Spring male flight began in mid-to late April and crawler emergence occurred in mid-to late May. Crawlers were active for a period of 6-7 weeks until early July. Peak crawler emergence occurred approximately 12 days after the first emergence, or 42 days after the first males were captured on pheromone traps. Because in our 3-year study the crawler emergence occurred 29-31 days or 191-202 day-degrees (base 10.5°C) after the capture of the first male, we conclude that a consistent time-relationship exists between the two events. Two insecticide treatments, one three days after the first crawler appearance and another 10 days later (near peak crawler activity), provided the best control against the first generation of scale.